Classdojo Application as an Effort to Increase Knowledge Of Dental Health Maintenance in Adolescents - Izati, Siti Nuraini Putri; Lestari, Syifa Yulia; Alfaini, Rosyda Aufia Sanata (Journal Center of Excellent : Health Assistive Technology, 2025)
Background: Oral and dental health problems remain a significant issue in Indonesia, especially among adolescents. The low level of knowledge regarding oral hygiene practices is one of the main causes of the high prevalence of dental caries in individuals aged 15–18 years. Therefore, engaging and effective educational methods are needed to raise awareness and improve adolescents’ knowledge of oral health maintenance. Objective: This study aimed to effective the level of knowledge among adolescents before and after a health education intervention using the ClassDojo application. Method: This research employed a quasi-experimental design with a one-group pretest-posttest approach. The sample consisted of 33 adolescents selected through total sampling. Data were collected using pretest and posttest questionnaires distributed online via the ClassDojo application. Results: The study showed an increase in knowledge, from 48.5% in the moderate category before the intervention to 93.9% in the good category after the intervention. Conclusion: Health education using the ClassDojo application is effective in improving adolescents’ knowledge of oral and dental health maintenance.